Antimicrobial Activities of the Ethanol Extracts of Capsicum Fruits with Different Levels of Pungency - Soediro Soetarno; Sukrasno Sukrasno; Elin Yulinah; Sylvia Sylvia (Institut Teknologi Bandung, 1997)
Ethanol extracts of the fruits of three kinds of Capsicum showed similar potencies in their antimicrobial activities against Gram (+) and Gram (-) bacterias, and fungi, although they contained different level of capsaicin. Bioautographic tests demonstrated that capsaicin was the main antimicrobial component. At least two other non-polar components of ethanol extract also contributed in the antimicrobial activity and very likely that these compounds were responsible for the activity toward Pseudomonas aeruginosa.